Spot on for liars! How public scrutiny influences ethical behavior - Ostermaier, Andreas; Uhl, Matthias (PloS one, 2017)
We examine whether people are more honest in public than in private. In a laboratory experiment, we have subjects roll dice and report outcomes either in public or in private. Higher reports yield more money and lies cannot be detected. We also elicit subjects' ethical mindsets and their expectations about others' reports. We find that outcome-minded subjects lie less in public to conform with their expectations about others' reports. Ironically, these expectations are false. Rule-minded subjects, in turn, do not respond to public scrutiny. These findings challenge the common faith in public scrutiny to promote ethical behavior. While public scrutiny eventually increases honesty, this effect is contingent on people's mindsets and expectations.